Slaves without slavery: the instability of servile exploitation in the Burgundian kingdom (Circe de clásicos y modernos, 2018)
This article examines slavery in the Burgundian kingdom. More precisely, it is suggested that despite the evidence of the existence of a large amount of slaves it is not appropriate to support the thesis of the survival of a stable slavery system in the region and period under study. The work is based primarily on the analysis of legislative sources.
Keywords: slaves; peasants; laws; Burgundian kingdom; Early Middle Ages